RESEARCH ON ENGLISH ACROSS CURRICULUM: AN OVERVIEW OF WHAT WE INVESTIGATE AND HOW - Agustinus Ngadiman (Widya Mandala Surabaya Catholic University, 2017)
This paper is an overview of empirical studies on language across curriculum. The emphasis of the review is on the ‘what’ and ‘how. The ‘what’ deals with the research areas and purposes. The ‘how’ deals with the approach and technique, setting and participants to set out the research. The purpose of the discussion that follows is to help us see what has been studied and how it has been researched. These discussions should help content and language specialists identify the range of factors related to English across the curriculum. The purpose of this paper is two-folds: to present important research model in English across curriculum and to suggest how insights from theory and research can be introduced in the classroom.